Chapter 7 Resisting Cultures of Inequality through Feminist Counter-Visuality Practices in Contemporary Spanish Fiction and Non- Fiction Cinema - Sánchez Espinosa, Adelina (Taylor & Francis, 2022)
This chapter aims to analyse feminist resistances to persuasion in visual discourse and to dissect several case studies in fiction and non-fiction Spanish films in order to highlight what we consider to be practices of feminist counter-visuality. Our theoretical genealogy starts with Adrienne Rich's and Judith Fetterley's claims for re-viewing and resisting readership. We then move from textual transgressions to the urge for visual transgressions expressed by feminist film theorists and practitioners. After discussing a classical example of persuasive visual discourse, Alfred Hitchcock's Psycho, and two instances of transgressive gazing by well-known feminist filmmakers Sally Potter and Jane Campion, we bring our argument to recent Spanish fiction and non-fiction cinema and close-read scenes from seven case studies as a basis to exploring how the alternative film discourses represented within them can operate as technologies of social response-ability and accountability in face of the challenges present in the current feminist agenda in Spain.